Sosialisasi Pemilahan Sampah sebagai Mitigasi Bencana Lingkungan di Asrama Khadijah Bantul Yogyakarta - Rita Mulyandari; Pramesta Praba Sumedi; Azri Novadli; Fithart Salman Fathrizky; Pinta Prasetya; Iksan Mahendra; M. Indra Setiawan (Jurnal Pengabdian Teknik dan Sains (JPTS), 2026)
Waste problems are one of the main factors contributing to environmental disasters, such as flooding, soil pollution, and the decline in water quality. Improper waste management, particularly in communal residential environments such as dormitories, may increase environmental disaster risks if waste segregation is not implemented at the source. This community service activity aimed to enhance the knowledge and awareness of residents of Khadijah Dormitory in Piyungan, Bantul Regency, Yogyakarta, regarding the importance of waste segregation as an environmental disaster mitigation effort. The methods applied included socialization and education through lectures, interactive discussions, demonstrations, and hands-on practice of waste segregation based on waste types, namely organic, inorganic, and hazardous waste. The results indicated an improvement in participants understanding and skills in proper waste segregation, as well as increased awareness that waste management plays a preventive role in environmental disaster mitigation. The integration of Islamic values, such as cleanliness and environmental responsibility, further strengthened positive behavioral changes among participants. However, challenges remained, including limited supporting facilities and inconsistent implementation. Therefore, continuous assistance and institutional support are necessary to ensure the sustainable application of waste segregation practices.